A feasibility study for electron-muon correlations at ALICE - Nathanson, Nina (Department of Physics, 2025)
A Feasibility Study for Electron-Muon Correlations at ALICE Nina Nathanson, February 2024 This analysis aims to assess the feasibility of using e-μ pairs as an alternative dilepton probe for heavy quark studies in proton-proton collisions. The e-μ channel would provide a much cleaner/low background signal than other currently-utilized probing methods, but it is statistics-limited, a re-striction which is of increased concern at ALICE due to the detector's geometry. With the use of Pythia simulations, the viability of undertaking an analysis of the channel using ALICE p-p data from LHC Run 3 is considered. The analysis finds that it is feasible to undertake a data study of the e-μ pairs and presents an estimate of the expected signal in a year of Run 3 data.